Effect of silicone oil additive on swelling stress alleviation in the metal hydride reactor. (28th February 2022) - Li, Qiunie; Tang, Gao; Cai, Bingchao; Wu, Kuojin; Qin, Laishun; Chen, Da; Huang, Yuexiang
Abstract: Considerable swelling stress associated with hydrogen absorption process caused by metal hydride expansion is extensively observed in a metal hydride tank which is usually designed for hydrogen storage application. Such swelling stress being applied to tank wall may cause potential safety issue such as tank failure. In the present investigation, silicone oil is selected as an additive incorporating into MlNi4.5 Cr0.45 Mn0.05 alloy in an attempt to alleviate the swelling stress. The results obtained by a self-built direct swelling stress testing apparatus show that the addition of silicone oil can significantly reduce alloy particle swelling stress. The addition of 3 wt% silicone oil is appropriate to acquire efficient swelling stress alleviation. During cycling the maximum swelling stress increases with charging pressure. The formation of silicone oil thin film on the surface of alloy particles, acting as a "cushion" among alloy particles, would reduce particle agglomeration and enhance particle movement during hydrogen absorption and desorption cycling. This is the reason for the observed swelling stress alleviation by silicone oil. Highlights: Swelling stress was reduced by addition of silicone oil. The maximum swelling stress increased with charging pressure. The swelling stress alleviation was ascribed to oil thin film on particle surface.